2018
DOI: 10.1063/1.5041905
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short-term solar irradiance forecasting methods when weather conditions are complicated

Abstract: Although the output of a photovoltaic power generation system is significantly positively correlated with solar irradiance, the latter variable is intermittent, random, and volatile. Volatility in solar irradiance is particularly marked when weather conditions are complex, and so, this factor has proved to be difficult to predict. A neural network (NN)-based approach is applied for short-term predictions in this study based on a timescale that encompasses the amount of irradiance each hour throughout the next … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The distributed photovoltaic system has the characteristics of intermittent, random and volatility, which is reflected in the distribution of solar irradiance in different seasons and weathers. Yu et al [26] demonstrated in previous work that RNN has better prediction performance than BPNN and RBFNN in sunny, rainy and cloudy days. LSTM, as the deep structure of RNN, is a solution for vanishing gradient and exploding gradient caused due to its special hidden layer cell structure design, which allowed the RNN models with LSTM units to model both short and long term temporal dependencies in time-series data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distributed photovoltaic system has the characteristics of intermittent, random and volatility, which is reflected in the distribution of solar irradiance in different seasons and weathers. Yu et al [26] demonstrated in previous work that RNN has better prediction performance than BPNN and RBFNN in sunny, rainy and cloudy days. LSTM, as the deep structure of RNN, is a solution for vanishing gradient and exploding gradient caused due to its special hidden layer cell structure design, which allowed the RNN models with LSTM units to model both short and long term temporal dependencies in time-series data.…”
Section: Discussionmentioning
confidence: 99%
“…An RNN is considered to be an effective tool for time-series data prediction. Yu et al [26] demonstrated in previous work that RNN has better prediction performance than backpropagation NN (BPNN) and radial basis function NN (RBFNN) in sunny, rainy and cloudy days. To improve the prediction accuracy, more variables and longer time series need to be added.…”
Section: The Incorporation Of Unstablementioning
confidence: 99%
“…Furthermore, the performance of forecast model has been enhanced by ensembling the extracted optimized features of different models. Yu et al analysed Elman NN (ENN), Radial Basis Function (RBF), and backpropagation NN (BNN) approaches on per hour forecasting horizon with different meteorological parameters. To evaluate the performance under different weather condition, data samples have been taken from different seasons of the year.…”
Section: Solar Forecastingmentioning
confidence: 99%
“…Photovoltaic (PV) panels are the biggest driving force in the rapid growth of solar power generation [2]. However, PV systems are susceptible to environmental factors such as sunlight, season, and geographic location, resulting in the PV characteristics of being stochastic, intermittent, and variable [3], [4]. These characteristics are required to reduce the efficiency of PV output [5].…”
Section: Introductionmentioning
confidence: 99%